Successful ablation of double accessory pathways: a rare case of coexistence between right inferoseptal WPW and left lateral AVRT - Yudha, Ardi; Ardhianto, Pipin (Universitas Brawijaya, 2024)
BACKGROUND: Managing double accessory pathways (APs) in the clinical setting presents significant challenges, primarily due to the rarity of this condition and the complexities involved in both diagnosis and treatment.CASE PRESENTATION: A 51-year-old male presented with recurrent episodes of palpitation. Electrocardiography (ECG) revealed sinus rhythm with a pre-excitation pattern characterized by a delta wave morphology showing a negative deflection in V1, a transitional zone in V2, and negativity in lead III and aVF, indicating an accessory pathway through the right infero-septal pathway. Further evaluation with electrophysiological study (EPS) confirmed the presence of accessory pathways, with the right infero-septal pathway exhibiting pre-excitation during sinus rhythm. Radiofrequency ablation (RFA) successfully eliminated the right infero-septal accessory pathway. Subsequently, coronary sinus propagation shifted from a concentric to an eccentric pattern, indicating another accessory pathway from the left lateral region. Another mapping was performed retrogradely at the mitral annulus, revealing ventriculoatrial (VA) fusion at the left lateral area and demonstrating inducible atrioventricular reentrant tachycardia (AVRT). RFA successfully eliminated the left lateral accessory pathway, with the final result showing retrograde block.CONCLUSION: This case highlights the importance of thorough diagnostics and tailored treatment strategies in managing dual APs, emphasizing the effectiveness of EPS-guided RFA for complex arrhythmias.